Midwives' perceptions of and attitudes towards prevention of mother-to-child-transmission of HIV - Rita Opoku-Danso; Debbie S.K. Habedi (AOSIS, 2023)
Background: Prevention of mother-to-child transmission (PMTCT) of HIV services has become an integral part of antenatal services. Prevention of mother-to-child transmission was introduced in all the regions of Ghana, but mother-to-child transmission (MTCT) continued to increase. Objectives: To explore and describe midwives' perceptions and attitudes towards PMTCT of HIV services. Method: Quantitative research approach and descriptive cross-sectional design were used. The population includes all midwives between the ages of 21 and 60 years who work in antenatal care (ANC) clinics in 11 district hospitals in the Central Region of Ghana where the study was conducted. Forty-eight midwives were interviewed using a census sample process. Data were analysed using the Statistical Package for the Social Sciences version 21. Correlation analysis was performed to find the relationships between the attitudes and the perceptions of the midwives on PMTCT of HIV services. Results: Seventy percent of midwives had positive perceptions of PMTCT of HIV services and 85% had positive attitudes towards the provision of PMTCT of HIV services. Midwives were screening all pregnant women who visited the ANCs and referring those who tested positive to other institutions where they can be monitored. Some of the concerns considered were views on retesting HIV-infected pregnant women throughout their pregnancy. There was a positive correlation between attitudes and perceptions of midwives on PMTCT of HIV services. Conclusion: Midwives had positive perceptions and positive attitudes towards the PMTCT of HIV services that they were providing to antenatal attendees. Also, as the attitudes of the midwives towards PMTCT of HIV services improved, their perceptions of PMTCT services also improved. Contribution: Decentralisation of PMTCT of HIV services to community-based health facilities is appropriate to enable sub-district health facilities to test for HIV and provide counselling services to pregnant women.